1998
DOI: 10.1103/physrevb.58.14113
|View full text |Cite
|
Sign up to set email alerts
|

Structural transformations at the surface of the decagonal quasicrystalAl70Co15Ni

Abstract: By using Auger electron spectroscopy and secondary-electron imaging, we show that, as a result of bombardment with 1.5-keV Ar ϩ ions, Al is preferentially sputtered and the surface structure of a decagonal Al 70 Co 15 Ni 15 quasicrystal transforms to body-centered cubic. Annealing the sample at 700 K restores the Al concentration at the surface and, thereby, the quasicrystalline structure. Real-time observations establish the orientational relationship between the quasicrystalline and cubic surface structures,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 20 publications
3
21
0
Order By: Relevance
“…Strong epitaxial relationships exist between the icosahedral bulk and the decagonal overlayer. The decagonal XPD pattern resembles the XPD [33] and secondary electron imaging (SEI) [34] patterns taken from d-Al-Ni-Co. Note that the SEI pattern of the decagonal metastable Al 22 Pd 56 Mn 22 overlayer resembles the sputtered d-Al-Ni-Co surface [19].…”
Section: -1mentioning
confidence: 76%
“…Strong epitaxial relationships exist between the icosahedral bulk and the decagonal overlayer. The decagonal XPD pattern resembles the XPD [33] and secondary electron imaging (SEI) [34] patterns taken from d-Al-Ni-Co. Note that the SEI pattern of the decagonal metastable Al 22 Pd 56 Mn 22 overlayer resembles the sputtered d-Al-Ni-Co surface [19].…”
Section: -1mentioning
confidence: 76%
“…Rouxel et al pointed out that sputtering in UHV moves the surface composition toward the region of a CsCl phase in the Al-Cu-Fe phase diagram. 19 Zurkirch, Erbudak, and Kortan observed a cubic phase induced by Ar ϩ sputtering on decagonal Al-Ni-Co. 21 In a similar vein, Naumovic reported that Al depletion induced by high-temperature annealing could produce a CsCl-type structure on the fivefold surface of i-Al-Pd-Mn. 18,22 These findings are all qualitatively similar to results generated within scientific communities outside of surface science.…”
Section: Introductionmentioning
confidence: 87%
“…[15][16][17][18] Similar observations-Al depletion upon Ar ϩ sputtering-have been reported also on two other Al-rich alloys, i-Al-Cu-Fe, ͑Refs. 19 and 20͒ and decagonal Al-Ni-Co. 21 In the bulk phase diagrams, the Al-based icosahedral alloys often have a CsCl-type structure on the Al-poor side. Rouxel et al pointed out that sputtering in UHV moves the surface composition toward the region of a CsCl phase in the Al-Cu-Fe phase diagram.…”
Section: Introductionmentioning
confidence: 99%
“…Secondary-electron imaging was used to study the decagonal surface of d-Al 70 Co 15 Ni 15 (Zurkirch, Bolliger, Erbudak, Kortan, 1998). It was shown that the Al depletion caused by 1.5-keV Ar þ -ion bombardment leads to a phase transformation into a disordered B2-phase.…”
Section: Surface Studies Of Decagonal Phasesmentioning
confidence: 99%